Effectiveness of hand splints on upper limb skills and functional activities in children with cerebral palsy: a review - Kumari, Rohina; ., Surbhi; Saharawat, Sakshi (International Journal Of Community Medicine And Public Health, 2021)
Cerebral Palsy is a non-progressive neurological disorder in which children may experience similar physical limitations, including those related to upper limb skills that affect the child's ability to participate in age-specific activities. The use of hand-splints in children with neurological conditions is little reported, they continue to be widely used to improve upper limb skills and functional activities. This review was done to investigate the use and effects of hand splints in Cerebral Palsy patient as orthotic treatment found to be very positive result in correcting and maintaining the achieved results. Electronic database search was conducted using Google scholar, Science direct, Pub Med, Cochrane Library and reference lists from all retrieved articles. Common problems in upper limb due to CP are flexion contractures of the fingers and wrist due to spasticity, pronation deformity of the forearm, thumb-in-palm deformity and hand-related disabilities, all lead to decrease in grip and muscle strength. Hand splints are often used to help a weak or ineffective joint or muscle to enhance a person's arm or hand posture, mobility, quality of motion, and function. The findings suggest that children with CP experience increased grip strength and fine motor dexterity when using different hand splints. This review summarizes the present state of understanding the extent to which orthotic management in CP can improve in the patient’s skills and functional activities by improving the muscle strength and hand function, also offers clinical suggestions for prescribing orthosis in order to optimize efficacy.